The Effectiveness of Animation Film Media to Know Ability Mathematical Concept of Early Childhood Based on Gender - Handayani, Sri; Haryono, Haryono; Ahmadi, Farid (Universitas Negeri Semarang, 2020)
The background of the research is how to low ability to recognize mathematical concepts of early childhood. The low ability is due to the use of instructional media which is less enjoyable for children when playing and learning in class. Gender of boys and girls may have different orientations in playing and in recognizing mathematical concepts. The purpose of this study is to analyze the differences in the influence of the use of animated films and animation on the ability to recognize mathematical concepts, analyze the differences in the influence of gender on the ability to recognize mathematical concepts, and analyze the interaction between animated films and gender in their effects on the ability to recognize mathematical concepts early childhood. This research uses a quantitative method with a quasi-experimental design using Factorial (2x2). A population of 151 children with a purposive sampling technique obtained a sample of 105 kindergarten B children in the Dahlia PAUD cluster in Batangan’s Kecamatan. The collecting of data in this study from the results of observations and tests and analyzed using two-way ANOVA. The results showed, there were differences in the influence of the use of animated films and animation, F = 17.546 in sig. 0.001, there is a difference in the influence of gender, F = 5.399 with sig. 0.022 and there is no interaction between animated films with gender differences in the ability to recognize mathematical concepts in early childhood, F = 0.130 with sig. 0.719. This research can be used as an alternative in choosing fun learning media to introduce mathematical concepts in early childhood.